PROTEIN DEFICIENCY AND POST-NATAL DEVELOPMENT OF THE SPINAL CORD OF WHITE RAT RATTUS NORVEGICUS: A HISTOLOGICAL AND HISTOCHEMICAL STUDY - SHARMA, DEEPAK; SHARMA, S. P. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1985)
The present study deals with the histological and histochemical effects of protein - deficiency on the post-natal development of the spinal cord of white rats, Rattus norvegicus. The paper attempts to decipher clearly the alterations in body length, tail length, spinal cord length, cytomorphology, differentiation of gray and white matters, central canal as well as dorsal and ventral horns in pups born to protein-deficient mothers. Alterations caused by protein deficiency in lipids, carbohydrates and proteins containing-SS groups during post-natal development of the spinal cord, in the light of histochemical observations, have hardly been studied by many of the earlier workers.